Effectiveness of an individually-tailored computerised CBT programme (Deprexis) for depression: A meta-analysis. (October 2017) - Twomey, Conal; O'Reilly, Gary; Meyer, Björn
Abstract: Computerised cognitive behavioural therapy (cCBT) programmes differ widely but have rarely been evaluated separately through meta-analysis. Through a meta-analysis of randomised controlled trials, we investigated the effectiveness of 'Deprexis', an unconventional and individually-tailored cCBT programme for depression. Comparisons from eight studies ( N = 2402) demonstrated the effectiveness of Deprexis for depressive symptoms at post-intervention, with a medium effect size ( g = 0.54, 95% CI: 0.39–0.69). Analogous results arose when study quality, screening, and randomisation procedure were taken into account. The level of guidance provided alongside Deprexis had a statistically non-significant impact upon the effect size. There was no significant difference in the performance of Deprexis in developer-led trials compared with non-developer trials, and no publication bias was detected. The weighted-average dropout rate for participants allocated to Deprexis treatment arms in included studies was 26.5%. Based primarily on trials in naturalistic community settings, the findings support the effectiveness of Deprexis for depressive symptoms. The positive findings add to the growing evidence-base for individually-tailored cCBT programmes and point to the need for further investigations of apparent systematic differences in the effectiveness of specific cCBT programmes. Highlights: Computerized CBT (cCBT) programmes differ widely but have rarely been evaluated separately through meta-analysis. Deprexis is a tailored cCBT programme for depression with unique features, justifying a programme-specific meta-analysis. Comparisons from 8 studies demonstrated effectiveness of Deprexis for depression reduction ( g =0.54, 95% CI: 0.39–0.69). The weighted-average dropout rate for participants allocated to Deprexis treatment arms was relatively low (26.5%). The positive findings for Deprexis add to the growing evidence-base for individually-tailored cCBT programmes.